2021
DOI: 10.1002/rmb2.12382
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between follicular size and developmental capacity of oocytes under controlled ovarian hyperstimulation in assisted reproductive technologies

Abstract: Purpose We investigate the relationships between oocyte developmental capacity and follicular size of its origin in Japanese women: those undergoing conventional IVF (cIVF) and ICSI, respectively. Methods A total of 3377 follicles were punctured separately and were classified into three groups (large, medium, and small) by their diameters. A total of 1482 retrieved oocytes were individually cultured and received cIVF or ICSI. The oocytes receiving ICSI were denuded and the number of mature (MII) oocytes was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…In our follicle models, the Polygon and Inverted-trapezoid models had the highest CLBR in comparison with the other models, and the proportion of mature oocytes in these models was higher than that in the other models. This is consistent with a study suggesting that the proportion of MII oocytes was signi cantly lower in small follicles (<13 mm) than in large follicles (≥16 mm), but with no difference in fertilization [29]. Previous studies have also reported lower oocyte recovery, reduced MII oocyte rates, and normal fertilization rates in small follicles [3,30,31].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our follicle models, the Polygon and Inverted-trapezoid models had the highest CLBR in comparison with the other models, and the proportion of mature oocytes in these models was higher than that in the other models. This is consistent with a study suggesting that the proportion of MII oocytes was signi cantly lower in small follicles (<13 mm) than in large follicles (≥16 mm), but with no difference in fertilization [29]. Previous studies have also reported lower oocyte recovery, reduced MII oocyte rates, and normal fertilization rates in small follicles [3,30,31].…”
Section: Discussionsupporting
confidence: 91%
“…The highest number of viable embryos in the Polygon model may be due to the higher proportion of mature oocytes. This is supported by previous ndings [29][30][31] that the proportion of mature oocytes is correlated with follicular size. In the Polygon model, moderate follicles (diameter 16-18 mm) accounted for the largest group, and there was less likelihood of receiving "post-mature" oocytes than in the Inverted-trapezoid model, which has 25% follicles that are too large (>20 mm).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found that MII oocyte rate, FOI, and FORT were the most important predictor variables in predicting euploid. Previous research suggested the MII oocytes rate from large follicles is significantly higher than from small follicles [ 13 ]. MII oocyte rate rather than the number of oocytes retrieved is a more accurate predictor of implantation and clinical pregnancy in IVF cycles [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Controlled ovarian hyperstimulation (COH) was performed using standard gonadotropin releasing hormone agonist (GnRHa)/follicle-stimulating hormone (FSH) protocols, as we reported previously [ 53 ]. Nasal spray GnRHa (900 μg/day) was given from the mid-luteal phase in the previous cycle to continuously suppress pituitary gonadotropin secretion until the injection of HCG (10,000 IU).…”
Section: Methodsmentioning
confidence: 99%